AKTUALISASI SPIRIT ISLAM NUSANTARA DAN ISLAM BERKEMAJUAN, DUA INSTRUMEN PENANGKAL ARUS RADIKALISASI PENEGAK NEGARA DEMOKRASI - Ahmad Fahrur Razi (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2020)
The emergence of radical notions in the ideology of the Ummah is a public phenomenon that must be eradicated from the minds of mankind, because this understanding can present a negative impact that can disturb the condition of social people which lead to acts of terrorism. This action occurs because the majority of radical groups tend to respond to religious normative texts in a written manner without any further analysis, so that there is a stagnation of the interpretations in their mindset. Indonesia itself is one of the countries that adopts the notion of democracy as a principle of citizenship and constitutionality, but on the other hand the unity of Indonesian is weak and vulnerable to radical understanding which is increasingly attacking the solidarity of the country's integration. This can be seen by reflecting on the active actions of religious radicalization and terrorism in Indonesia which have been ongoing, especially entering the early 21st century. Therefore, in response to the presence of phenomenology, the author tries to present a counteractive response as an antithetical refutation of the argument. That is an effort to counteract the radical notion, the author tried to explain the views of two major assemblies of Muslim organizations in the country, namely NU with the spirit of Islamic Nusantara and Muhammadiyah with Islamic Spirit Progressing (Islam Berkemajuan), by using paradigm- comparative analysis method between both of them. Where the results are found that both are indigenous products, which is where Islam Nusantara is a spirit that tends to ukhuwahwataniyah as a multicultural people while Islam progresses towards social modernism. With the final conclusion, the two spirits did not at all mention the negative radicalist doctrines, but explicitly oriented to the movement of tolerance, moderation and contextualization which led to the upholding of democratic values in the Indonesian country.